Assessing 5-year follow-up of core outcome set uptake for Bronchiectasis and Hidradenitis Suppurativa: a review of trial registry entries - Paula R Williamson; Susanna Dodd; Charlotte Shorey (BMJ Open)
Objective If clinical trials measure and report the outcomes included in core outcome sets (COS) for a given condition/disease as a minimum, this has the potential to improve comparability between trials and prevent research waste. Until now, the uptake of the Bronchiectasis and Hidradenitis Suppurativa (HS) COS has not been assessed.This study assessed the uptake of Bronchiectasis and HS COS using a review of trial registries, with entries taken from ClinicalTrials.gov and the WHO International Clinical Trial Registry Platform. This uptake assessment provides valuable information to inform COS refinement and uncover areas lacking uptake to inform further dissemination requirements.Methods For each trial, the outcomes included in the trial registry entry were extracted and compared with those included in the corresponding Bronchiectasis or HS COS. The Bronchiectasis COS consists of 18 outcomes, and the HS COS, 6.Results Of the trials registered after both COS were developed in 2018, 63% (12/19) of HS trials planned to measure the full COS, whereas for Bronchiectasis, 0% (0/24) of trials planned to measure the full COS. However, of the five priority outcomes to be measured for Bronchiectasis, 4% (1/24) of trials planned to measure all five outcomes.Both COS publications’ focus was to reach consensus on what outcomes should be measured. Despite both publications referring to the Core outcome Measures for Effectiveness Trials (COMET) Handbook, which discusses the importance of COS dissemination, implementation plans were not included in either publication.Conclusions The results suggest that uptake of the HS COS is relatively good, despite yearly fluctuations, whereas for Bronchiectasis, COS uptake is limited. Further research into standardised measurement tools for HS is expected to increase uptake. The focus for Bronchiectasis, however, will be to refine the COS for feasible application in clinical trials. Future COS development publications should use all resources from the COMET initiative to ensure feasible dissemination of the COS.